1991
DOI: 10.1159/000186285
|View full text |Cite
|
Sign up to set email alerts
|

Application of P-31 Nuclear Magnetic Resonance Spectroscopy to a New Experimental Kidney Perfusion Model Using Cadaveric Porcine Kidneys from Slaughterhouse

Abstract: Larger NMR magnets with relatively high field strengths have become available recently, allowing the application of magnetic resonance spectroscopy (MRS) in larger mammalian organs. The aim of this study was to develop and test a new and simple kidney perfusion model from slaughterhouse swine using a new 4.7-tesla/40-cm diameter system, with the intention behind to provide a human-like mammalian experimental kidney perfusion model, and to avoid sensitive in vivo animal experiments on higher-developed mammalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This requires additional hardware, which is not available on our current setup. 31 P ATP synthesis has been demonstrated in the past, under arterial blood perfusion applied immediately after kidney harvesting [26], but this model has no clinical application. In our study, we show that ATP can be detected by 31 P CSI under fully clinical kidney preservation conditions, if appropriate O 2 tension is applied to the preservation medium.…”
Section: Discussionmentioning
confidence: 99%
“…This requires additional hardware, which is not available on our current setup. 31 P ATP synthesis has been demonstrated in the past, under arterial blood perfusion applied immediately after kidney harvesting [26], but this model has no clinical application. In our study, we show that ATP can be detected by 31 P CSI under fully clinical kidney preservation conditions, if appropriate O 2 tension is applied to the preservation medium.…”
Section: Discussionmentioning
confidence: 99%
“…This technology is compatible with magnetic resonance spectroscopy (MRS) 9 . Consequently, it is possible to evaluate the viability of the organs during their perfusion by measuring ATP resynthesis, which is an absolute proof of organ viability 10,11 . The main marker of mitochondrial dysfunction is ATP depletion, which leads to apoptosis by activation of proaptotic capsase enzymes 12 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously demonstrated that slaughterhouse pig kidneys may serve as a model of the metabolic states of human kidney grafts (10). Pig kidneys are more sensitive to hypothermia and reperfusion injury than human kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Human renal grafts are rarely available for studies on graft deterioration, but it has been shown that pig kidneys obtained from a slaughterhouse serve as valid models for studies of metabolite kinetics (8,10).…”
Section: Introductionmentioning
confidence: 99%